Работы 2009 г. на Западном укреплении Бельского городища - Шрамко, И.Б. (Археологічні дослідження в Україні, 2010)
Presented are the preliminary results of 2009 excavations at the burnt mound 10 in the Western fortification of Bilsk hillfort, in the central part of which dwelling and husbandry structures from the second half of the 7th c. to the first quarter of the 4th c. BC were discovered.